3D and 4D printable dual cross-linked polymers with high strength and humidity-triggered reversible actuation. Issue 15 (2nd July 2021) - Jiang, Zhen; Shen, Peidong; Li Tan, Ming; Yan, Qiao; Viktorova, Jekaterina; Cementon, Chiara; Peng, Xiaotong; Xiao, Pu; Connal, Luke A.
Abstract : We report a macromolecular design concept to develop humidity-responsive polymers with simultaneously improved mechanical properties and 3D printability, while still displaying fast, reversible and complex shape transformations. Abstract : It is highly desirable but challenging to develop humidity-responsive polymers with simultaneously improved mechanical properties and 3D printability, while still displaying fast, reversible and complex shape transformations. Herein, a facile and scalable supramolecular strategy of fabricating a new class of humidity-responsive polymers is proposed to address this issue. The multiple hydrogen-bond cross-linked network is used to provide high humidity sensitivity and shear-dependent rheological behavior. Further introduction of metal coordination bonds can not only improve mechanical strength and creep resistance, but also promote reversible humidity-driven actuation and generate viscoelastic hydrogel inks. This humidity-responsive polymer with these unique combined attributes enables the potential to fabricate diverse functional materials from artificial muscles, smart electronic and catalytic devices. Moreover, diverse arbitrary architectures with spatial thickness contrast exhibiting sophisticated biomimetic 4D printing process were manufactured by direct ink writing (DIW). This material and method not only provides a general route to tune versatile functionalities and intelligent responsiveness of polymeric actuators at the molecular level, but also provides new opportunities for building exceptional 4D printed products.